Kesalahan Berbahasa Tataran Sintaksis Pada Penulisan Pengalaman Pribadi Siswa Kelas X SMA Bakti Negara - Yustina Sako; Roekhan Roekhan; Sunoto Sunoto (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to describe the level of syntax errors that include aspects of phrases and sentences on writing personal experience grade X SENIOR HIGH SCHOOL Stella Gratia Atambua. This research uses qualitative research designs with the kind of descriptive research. The results of this study indicate that many students make a mistake on a sentence structure that covers ten aspects. These findings prove that students pay attention to the use of grammar in writing, lack of vocabulary which belonged to the students, the influence of the use of local languages, and teachers less use of grammar in writing.